Emerging Frameworks in Health and Education: Conceptual Evolution in Pursuit of School-Based Health - Daniel Skinner; Hannah Palme’; Sara Bode; Mary Kay Irwin (Continuity in Education, 2023)
This paper presents a historical account of the development of key concepts at the intersection of American education and health. Beginning with early advancements from the Association for Supervision and Curriculum Development and the World Health Organization, the authors show the movement from early considerations of the codependency of health and education, as well as educational revisions of more-familiar “social determinants of health” frameworks, culminated more than fifty years later, with the 2014 introduction of “Whole School, Whole Community, Whole Child” (WSCC). At the same time, the authors show that the trajectory of this movement, consisting of efforts to work through differences in how institutions and experts approach health and education, was far from linear, consisting instead of fits and starts. In addition to explaining why WSCC is in many ways a critical revision of social determinants models that serves today as a promising foundation of American school-based health, the authors examine opportunities and challenges that the pivot towards WSCC presents, especially concerning assessment, funding, and collaboration.